Establishment of the epithelial attachment and connective tissue adaptation to implants installed under the concept of "platform switching": a histologic study in minipigs - Farronato, Davide; Santoro, Giacomo; Canullo, Luigi; Botticelli, Daniele; Maiorana, Carlo; Lang, Niklaus P. (Wiley-Blackwell, 2012)
Aim: To validate the platform switching concept at oral implants with respect to the preservation of the alveolar crestal bone levels in an animal model. Material & methods: Five minipigs received three implants each with a 0.25mm implant/ abutment mismatch and were placed flush (T(0)), 1 mm below (T(1)) and 1 mm above (T(+1)) the alveolar bony crest, and as a control, one conventionally restored implant placed at the bone level. The implants were randomly inserted flapless into the mandible. Four months after implant insertion, the animals were sacrificed, and undecalcified block sections were obtained and used for histological analyses. Results: The mean values for peri- implant bone resorption were 1.09 +/- 0.59mm (Control), 0.51 (+/- 0.27 mm, T(0)), 0.50 (+/- 0.46 mm, T(1)) and 1.30 (+/- 0.21 mm, T (+1)), respectively. Statistically significant differences (P< 0.05) were found among the test (T(0), T(-1)) and the control sites. Control implants presented an average biologic width length of 3.20mm (+/- 0.33), with a connective tissue adaptation compartment of 1.29mm (+/- 0.53) and an epithelial attachment of 1.91 mm (+/- 0.71). T(0), T(1) and T(+1) implants presented with a mean biologic width of 1.97mm (+/- 1.20), 2.70 mm (+/- 1.36) and 2.84mm (+/- 0.90), respectively, with a connective tissue adaptation compartment of 1.21mm (+/- 0.97), 1.21 mm (+/- 0.65) and 1.50 mm (+/- 0.70) and an epithelial attachment of 0.84 mm (+/- 0.93), 1.66 mm (+/- 0.88) and 1.35 mm (+/- 0.44), respectively. Differences between the configurations were mainly associated with the length of the epithelial attachment. The epithelial attachment was significantly longer in the C sites than in T(0) (P = 0.014). However, no other differences between configurations were detected. Conclusion: If the implants are positioned at the level of the alveolar bony crest, the platform switching concept may have a minor impact on the length of the epithelial attachment (0.84 vs. 1.91 mm), while the connective tissue adaptation compartment remains relatively unaffected. Moreover, platform switching resulted in less resorption of the alveolar crest (0.58 mm).
Keywords: biologic width; connective tissue adaptation; epithelial attachment; healing; oral implants; platform switching